Efficient sidelink re‐establishment scheme in device‐to‐device communications‐based public safety networks - W.J. Lee; H.S. Ryu; M.Y. Chung (Electronics Letters)
In cellular‐based public safety networks, user equipments (UEs) located in coverage area of active cells are able to act as relay UEs (RUEs). These RUEs provide cellular services to isolated UEs (IUEs). Due to mobility of both an IUE and a RUE, a link between them may be disconnected. Thus, it is necessary to newly establish a link between the IUE and another RUE. Unfortunately, it may cause that packets sent by previous RUE to be lost during the link re‐establishment procedure. An efficient sidelink re‐establishment procedure is proposed to reduce link re‐establishment set‐up delay. The performance of the proposed method compared with the conventional scheme used in 3rd Generation Partnership Project is evaluated. The proposed scheme shows better performance than the conventional scheme in terms of signalling overhead and set‐up delay for sidelink re‐establishment.